Prognostic value of KRAS subtype in patients with PDAC undergoing radical resection - Dai, Manxiong; Jahanzaib, Raja; Liao, Yan; Yao, Fengxuan; Li, Jia; Teng, Xiong; Chen, Kang; Cheng, Wei (Frontiers in Oncology, 2022)
Objective: To explore the frequency distribution of KRAS mutant subtypes in patients with resectable PDAC in China and then evaluate the prognostic value of different KRAS subtypes in patients with PDAC undergoing radical resection. Methods: The clinicopathological data and gene test reports of 227 patients undergoing PDAC radical surgery at Hunan Provincial People's Hospital from 1 January 2016 to 1 January 1 2020 were retrospectively evaluated. There were 118 men (52%) and 109 women (48%). The mean age was 58.8±10.3 years. After univariate analysis of the clinicopathological factors (sex, age, presence or absence of underlying disease, location of the primary tumour, tumour TNM stage, T stage, N stage, presence or absence of vascular invasion, presence or absence of nerve invasion, surgical margin, KRAS mutation subtype), variables with P < 0.1 were included in the multivariate Cox regression model analysis, and the log-rank sum test and Kaplan-Meier curves were used to assess the correlation of the KRAS mutation subtype with the overall survival time. Results: KRAS mutations were detected in 184 of 227 patients (81.1%) (G12D: 66; G12V: 65; G12R: 27; Q61:26) and were not detected in 43 patients (18.9%). KRAS mutations were associated with tumour differentiation (P = 0.001), TNM stage (P = 0.013), and T stage (P < 0.001). Multivariate Cox regression model analysis showed that N stage, surgical margin, tumour differentiation, and KRAS-G12D mutation were independent prognostic factors for DFS and OS. Patients with the KRAS-G12D subtype had shorter OS with a median OS of 12 months (HR: 0.55, CI: 0.39–0.77, P < 0.001), and patients with KRAS wild-type had longer OS with a median OS of 19 months (HR: 0.57, CI: 0.42–0.76, P < 0.001). Conclusion: KRAS wild-type individuals are more prevalent in the Chinese population than in European or American populations. Patients undergoing surgery had a reduced percentage of tumors with KRAS-G12D. When determining the prognosis of individuals with radically resected PDAC, reference markers for KRAS mutation subtypes can be employed.